Exploring the development of the mirror neuron system: finding the right paradigm - Shaw, Daniel J; Czekóová, Kristína (Developmental neuropsychology, 2013)
Due to its ability to map an observed action onto the observer's own cortical motor circuits, the mirror neuron system (MNS) has been implicated in many facets of social cognition. As such, achieving an understanding of the typical development of this intriguing brain system seems obvious. Only now, however, are studies attempting to explore the processes and principles behind the emergence of the MNS. This article critically reviews a number of experimental paradigms employed in this endeavor. We conclude by suggesting that future neuroscientific investigations should incorporate a response-stimulus procedure, whereby action execution results in, not from, novel sensory stimuli.
Keywords: zrcadlové neurony; Brain; elektroencefalografie; Electroencephalography; zvířata; mozek; Humans; Psychomotor Performance; Mirror Neurons; lidé; psychomotorický výkon; Animals